Assessing top management commitment, workforce management, and quality performance of Malaysian hospitals - Ahmed, Selim; Abd. Manaf, Noor Hazilah; Islam, Rafikul (Taylor & Francis Online, 2019)
The present study investigates top management commitment, workforce management and quality performance in Malaysian hospitals based on demographical information of the respondents. Aim of this study is to identify the difference or conformance on top management commitment, workforce management and quality performance of Malaysian hospitals with demographics such as gender, marital status, types of hospital and position. This study distributed 1007 self-administered survey questionnaires to hospital staff resulting in 438 useful responses with a 43.5% response rate. Research data were analysed based on reliability analysis, exploratory factor analysis (EFA), independent samples t-tests, one-way ANOVA and discriminant analysis using SPSS version 23. Findings of this study indicate that there is a significant difference between single and married hospital staff on workforce management of the Malaysian hospitals. Married respondent perceives workforce management more favourably compared to single. The findings also indicate that hospital nurses perceive workforce management and quality performance more favourably compared to other hospital staff (i.e. doctors, pharmacists, medical laboratory technologists). Moreover, this study conducted comparison analysis between public and private hospitals on top management commitment, workforce management, and quality performance. The research findings indicate that private hospitals have better top management commitment and workforce management compared to public hospitals in Malaysia.